State enterprise: business or politics? - Coombes, David L. (London ; Allen and Unwin [for] Political and Economic Planning, 1971)
This book examines a whole range of problems that include economic, political and administrative, to which nationalisation has given rise. It is a result of one of a series of studies of control of public expenditure in Great Britain undertaken. The book insists that the economic and social obligations of the nationalised industries reflect the general objectives of government policy for industry as a whole and are not peculiar to the nationalised industries.
Includes bibliographical references and index.
oo 16/08/2018
Loans
Keywords: Government business enterprises; Public interest